Penerapan Media “Bulletin Board” pada Pembelajaran Tematik di Kelas IV Sekolah Dasar untuk Meningkatkan Keaktifan Siswa - Marsanda Claudia Parameswara; Yayang Furi Furnamasari (Departement of Mathematics Education, 2023)
This study aims to determine the application of media bulletin board on thematic learning in the fourth grade of elementary school to increase the students ' creativity. This study uses the type of Class Action Research (PTK). The targets in this study were 11 elementary school students. The technique of data collection in this study is taken from the record of student's kekatif, evaluation test results, and interviews of teachers and students. The results showed that the application of media bulletin board on thematic learning can increase the activeness of students in learning. This can be seen from the results of the student activity table and evaluation in the second cycle which reached a very high category. In addition, the students ' creativity can also be seen from the enthusiasm of the students at the time of study. With the results obtained in the second cycle, it can be stated that the application of media bulletin board on thematic learning can increase the activity of students in learning.